Environmental risk factors in the aetiology of multiple sclerosis in Kayseri: a case control study - Servin Yeşil Günal; Meral Mirza (Epidemiology, Biostatistics and Public Health)
Background: our purpose is to evaluate the possible relationship between multiple sclerosis (MS) and environmental factors in Kayseri. Methods: this case control study was conducted on 100 patients with MS and 100 sex-aged and residential area matched control. Data was collected by using face to face interviews. Questionnaire consisted of two parts. The first part was comprised of items related with the participants’ sociodemographic features. The second part was related with factors thought to be involved in the occurrence or aggravation of the disease. The Chi-square test and logistic regression were used for analysis. Results: logistic regression analysis revealed the following as possible risk factors in MS cases: economic status (Odds Ratio (OR): 0.14 adjusted 7.19; Confidence Interval 95% (CI): 0.05-0.43), having a sensitive personality (OR:4.51; 95% CI: 1.10-18.45), familial history of MS (OR:3.28; 95% CI: 1.3-8.27), history of cranial and spinal injury (OR: 2.99; 95% CI: 1.11-8.08), cooking oil consumption (OR:0.07 adjusted 13.5; 95% CI: 0.03-0.20), consumption of legumes and grains (OR: 0.11 adjusted 8.9; 95% CI: 0.03-0.41), and living in dwellings within a distance of 500 meters from transformer basestations (OR: 6.5; 95% CI: 1.54-28.21). Conclusions: we believe that it is necessary to inform the individuals about the risk of MS and their relatives of the results of large-scale joint studies and to offer suggestions based on the data obtained.